Vegeta Manufacturing Sdn. Bhd. / Adib Hazmi Marhalim - Marhalim, Adib Hazmi (Faculty Of Chemical Engineering, 2021)
They had used the knowledge and skills they learnt during college at their workplace. Besides, they had learnt their strengths and weaknesses. They able to cope their weakness through guidance by the supervisor as well as the employers of the company. Second, the internship helps to ] improve the students' communication skills through communicating and cooperating with the company's staffs. This internship program in Vegeta Manufacturing Sdn. Bhd. gave a great opportunity as a student. This subject helps me expand my mind on real life working experience after spending 17 weeks for this internship. Moreover, I had gained new experience and gain an input specifically in wastewater treatment plant, from start up to run until shut down of the plant. The supervisor is easy to communicate and easy to reach. Ms. Allison helps me to overcame any problems occurred during the whole internships. Furthermore, this internship program was able to let me handle and use the equipment in the plant and how optimization is applied in the whole process. This experience and knowledge are surely help me when graduating from University Teknologi Mara (UiTM) Pasir Gudang for completion my Diploma in Chemical Engineering.